Pengaruh Konsentrasi Gula Terhadap Karakteristik Fisikokimia dan Organoleptik Marmalade Pisang Tongka Langit - Priscillia Picauly; Mahfud J. Marshadu; Brihilda Auratu; Yunitha Andries; Meigrendi J. Rumahrenu; Lea Siatam; Belsy Erubun; Wahyuningsi Hamzah; Aulia Wailisa (Politeknik Negeri Ketapang, 2025)
Marmalade is a food product made from fruit juice and has a semi-solid texture. Marmalade can be made from tongka langit banana fruit with the addition of sugar, citric acid, pectin, and pieces of fruit skin. This study aims to determine the right sugar concentration in making tongka langit banana marmalade. This study used a Completely Randomized Design (CRD) with sugar concentration treatments of 50%, 55%, and 60%. Observations made included physicochemical tests of water content, total solids, vitamin C, and organoleptic tests including color, taste, texture, and spreadability. The results showed that the best 50% sugar concentration treatment with physicochemical characteristics of water content of 34.43%, total dissolved solids of 48.50 brix0, vitamin C 1.51 mg/100g, and organoleptic characteristics of color, taste, texture, and spreadability, which were preferred by panelists.